Determinants of family planning service uptake and use of contraceptives among postpartum women in rural Uganda - Sileo, Katelyn M.; Wanyenze, Rhoda K.; Lule, Haruna; Kiene, Susan M. (International journal of public health, 2016)
Uganda has one of the highest unmet needs for family planning globally, which is associated with negative health outcomes for women and population-level public health implications. The present cross-sectional study identified factors influencing family planning service uptake and contraceptive use among postpartum women in rural Uganda. Methods—Participants were 258 women who attended antenatal care at a rural Ugandan hospital. We used logistic regression models in SPSS to identify determinants of family planning service uptake and contraceptive use postpartum. Results—Statistically significant predictors of uptake of family planning services included: education (AOR = 3.03, 95 % CI 1.57–5.83), prior use of contraceptives (AOR = 7.15, 95 % CI 1.58–32.37), partner communication about contraceptives (AOR = 1.80, 95 % CI 1.36–2.37), and perceived need of contraceptives (AOR = 2.57, 95 % CI 1.09–6.08). Statistically significant predictors of contraceptive use since delivery included: education (AOR = 2.04, 95 % CI 1.05–3.95), prior use of contraceptives (AOR = 10.79, 95 % CI 1.40–83.06), and partner communication about contraceptives (AOR = 1.81, 95 % CI 1.34–2.44). Conclusions—Education, partner communication, and perceived need of family planning are key determinants of postpartum family planning service uptake and contraceptive use, and should be considered in antenatal and postnatal family planning counseling.
Keywords: Family Planning; Contraception; Uganda